2017
DOI: 10.1080/21645515.2017.1391433
|View full text |Cite
|
Sign up to set email alerts
|

Human cytomegalovirus vaccine development: Immune responses to look into vaccine strategy

Abstract: Human cytomegalovirus (HCMV) causes considerable morbidity and disability in high risk, immunocompromised populations including recipients of solid organ transplants, and fetuses whose immune systems are not yet mature. Vaccines aimed at ameliorating the severity of disease and preventing HCMV infection can be categorized into two main approaches of vaccine design, with one focusing on virus modification and the other on individual antigens. However, no candidates in either class have been successful in achiev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 126 publications
0
9
0
Order By: Relevance
“…Though the pentameric complex elicits a high titer of HCMV neutralization activity, the antibodies elicited are protective against HCMV infection of epithelial cells, endothelial cells and monocytes, but not fibroblasts or primary trophoblast progenitor cells [ 46 , 47 , 48 , 49 , 68 , 69 , 70 , 71 ]. It has been suggested that the combination of trimeric gB and pentameric complex proteins may be an optimal prophylactic HCMV vaccine [ 37 , 72 , 73 ]. The effect of gB in combination with pentameric complex has been evaluated using MVA vectored or RNA vaccine that simultaneously express gB and the pentameric complex [ 66 , 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…Though the pentameric complex elicits a high titer of HCMV neutralization activity, the antibodies elicited are protective against HCMV infection of epithelial cells, endothelial cells and monocytes, but not fibroblasts or primary trophoblast progenitor cells [ 46 , 47 , 48 , 49 , 68 , 69 , 70 , 71 ]. It has been suggested that the combination of trimeric gB and pentameric complex proteins may be an optimal prophylactic HCMV vaccine [ 37 , 72 , 73 ]. The effect of gB in combination with pentameric complex has been evaluated using MVA vectored or RNA vaccine that simultaneously express gB and the pentameric complex [ 66 , 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…Novel approaches for treatment of HCMV infections are areas of great research interest. No vaccines aimed at ameliorating the severity of disease and preventing HCMV infections have so far been successful in achieving durable and protective immunity [85, 86]. Several new promising vaccine strategies against HCMV have been developed and evaluated ex vivo and in animal models [82, 87, 88].…”
Section: Treatment Of Oncogenic Hcmv Infectionsmentioning
confidence: 99%
“…Asymptomatic seropositivity has also been linked to increased risk for age-related, chronic inflammatory pathologies, including vascular disease, frailty and immune dysfuntion [7][8][9][10][11] . Currently, there is no vaccine for HCMV, and antivirals fail to eliminate the latent reservoir of virus because the drugs only target actively replicating virus 12,13 .…”
Section: Introductionmentioning
confidence: 99%